Transformasi Budaya Suku Minangkabau di Perantauan: Studi Pustaka dalam Perspektif Antropologi Budaya - Putri, Riska; Suwandi; Aribowo, Pinkan Claudia; Rosyid, Nurfaizal; Ardhiansyah, Septian Syahnam (CV. Kurnia Grup, 2026)
The tradition of migration in Minangkabau society is not only a form of economic mobility, but also an expression of a complex and structured cultural value system. Migration opens up an interesting space for cultural transformation to be studied anthropologically, especially in the context of how Minang identity, social structure, and traditional values are managed outside their homeland. This study aims to analyze the cultural transformation of the Minangkabau in diaspora regions through a cultural anthropological approach using a literature review method. Data sources were obtained from scientific journals, reference books, and academic publications related to the Minangkabau diaspora. The findings indicate that despite shifts in cultural forms due to urbanization and globalization, Minang communities in diaspora continue to uphold core values such as matrilineal kinship, solidarity, and the interplay between traditional customs and Islam. Adaptation occurs through community organizations, cultural economic practices, and the use of digital media as spaces for transmitting values. Younger generations of the diaspora play a crucial role in maintaining identity continuity through contextual cultural innovations. These findings emphasize that Minangkabau culture is not static but capable of surviving and transforming with dignity in new social spaces. This study is relevant for strengthening strategies to preserve local culture in the context of migration and modernity.